The Effectiveness of The Tarl Learning Approach On The Ability To Master Underpassing In Volleyball At Darut Taqwa High School Purwosari, Pasuruan - Muhammad Saikhu Rakhman; Wiwik Kusmawati (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Volleyball is a complex game, not easy for everyone to do. Knowledge of basic techniques is required, including serving, passing, blocking, and smashing. The use of underhand passing in volleyball is very important because this technique is very dominant in the game. This study aims to determine the effect of the Teaching at the Right Level approach to improve underhand passing skills in grade X students of SMA Darut Taqwa Purwosari Pasuruan. This study was conducted using the Kemmis and Mc Taggart model through the stages of planning, implementation, observation, and reflection. The study was carried out in two cycles, starting with the pre-cycle stage to obtain a direct picture of underhand passing skills in students. The results of the pre-cycle stage were students whose scores were above the KKTP were only 19.44% or as many as 7 students. This value increased in the first cycle stage, namely students who got scores above the standard or KKTP to 16 students or as many as 44.44% of the total students. This result increased in the second cycle stage, namely to 31 students or around 86.11% of the total students. Thus, it can be concluded that the Teaching at the Right Level approach is effective in improving underhand passing skills in class X students of SMA Darut Taqwa Purwosari Pasuruan.